N-terminal acetylation of superoxide dismutase 1 accelerates amyloid formation without general destabilization of the apo state - Jensen, Kristine Steen (Protein Science, 2025)
Co- and post-translational modifications can significantly impact the structure, dynamics, and function of proteins. In this study, we investigate how N-terminal acetylation affects misfolding and self-assembly of the enzyme superoxide dismutase 1 (SOD1), implicated in amyotrophic lateral sclerosis (ALS). Studies of protein inclusions in patient samples and animal models have shown that wild-type SOD1 can form amyloid fibrils even when no mutations are found in the sod1 gene. This has identified SOD1 amyloid formation as a possible common denominator of ALS and may suggest that co- and post-translational modifications, like N-terminal acetylation found in human SOD1, can be a factor in disease development. In this work, the impact of N-terminal acetylation of SOD1 on stability and aggregation is characterized. Results show that the structure and thermal stability of the apo state are unaffected by the modification while the amyloid formation rate is significantly enhanced. This is caused by a shortening of the nucleation phase together with an increase of fibril elongation by more than 10-fold upon N-terminal acetylation of SOD1. Collectively, the findings demonstrate how regulation by co- and post-translational modifications can influence protein misfolding and self-assembly.
Publisher Copyright: © 2025 The Author(s). Protein Science published by Wiley Periodicals LLC on behalf of The Protein Society.
Keywords: amyloid formation kinetics; amyotrophic lateral sclerosis; N-terminal acetylation; post-translational modification; superoxide dismutase 1